Liver transplantation in patients with post-hepatectomy liver failure – A Northern European multicenter cohort study. Issue 7 (July 2022) - Sparrelid, Ernesto; Thorsen, Trygve; Sauter, Christina; Jorns, Carl; Stål, Per; Nordin, Arno; de Boer, Marieke T.; Buis, Carlijn; Yaqub, Sheraz; Schultz, Nicolai A.; Larsen, Peter N.; Sallinen, Ville; et al.
Abstract: Background: Liver transplantation (LTX) has been described as a rescue treatment option in severe, intractable post-hepatectomy liver failure (PHLF), but is not considered to be indicated for this condition by many hepatobiliary and transplant surgeons. In this article we describe the clinical experience of five northern European tertiary centers in using LTX to treat selected patients with severe PHLF. Methods: All patients subjected to LTX due to PHLF at the participating centers were identified from prospective clinical databases. Preoperative variables, surgical outcome (both resection surgery and LTX) and follow-up data were assessed. Results: A total of 10 patients treated with LTX due to severe PHLF from September 2008 to May 2020 were identified and included in the study. All patients but one were male and the median age was 70 years (range 49–72). In all patients the indication for liver resection was suspected malignancy, but in six patients post-resection pathology revealed benign or pre-malignant disease. There was no 90-day mortality after LTX. Patients were followed for a median of 49 months (13–153) and eight patients were alive without recurrence at last follow-up. Discussion: In selected patients with PHLF LTX can be a life-saving procedure with low short-term risk.